2021
DOI: 10.3233/bd-219009
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of phyllodes tumors of the breast from a single institution

Abstract: BACKGROUND: Phyllodes tumors (PTs) are rare fibroepithelial breast tumors with diverse biological behavior. OBJECTIVE: This study aimed to analyze the characteristics, management, and outcome of phyllodes tumors. METHODS: Patients diagnosed with PTs in our institution from January 2013 to December 2017 were identified retrospectively by the ICD-10 code. Data were collected from medical records. The diagnosis of this tumor was based on histopathological results. Variables analyzed included age, tumor site, surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
3
0
4
Order By: Relevance
“…Phyllodes tumors (PTs) of the breast are uncommon fibro epithelial lesions that account for less than 0.5% of all breast tumors. [1][2][3] PTs are a rare diagnosis among breast tumors. In our study we found that PTs was representing 1,36 % of all breast tumors in our department during the period of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phyllodes tumors (PTs) of the breast are uncommon fibro epithelial lesions that account for less than 0.5% of all breast tumors. [1][2][3] PTs are a rare diagnosis among breast tumors. In our study we found that PTs was representing 1,36 % of all breast tumors in our department during the period of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Phyllodes tumors (PTs) of the breast are uncommon fibro epithelial lesions that account for less than 0.5% of all breast tumors. [1][2][3] The World Health Organization (WHO) has classified PTs histologically as benign, borderline, and malignant. 4 They are also graded by WHO based on their histopathological characteristics including stromal hypercellularity and atypia, cellular pleomorphism, mitotic activity, and margin appearance.…”
Section: Introductionmentioning
confidence: 99%
“…La radioterapia adyuvante puede ser beneficiosa para reducir la recurrencia local y, a veces, se considera para tumores filoides malignos de alto riesgo, que incluyen aquellos con un tamaño superior a 5 cm, crecimiento excesivo del estroma o más de 10 mitosis por campo de gran aumento. (2,12,15) En general, la radioterapia ha demostrado tener un efecto positivo en el control local de la enfermedad, aunque no se ha observado un alargamiento de la supervivencia. (3) En cuanto a la quimioterapia, se ha utilizado para la enfermedad recurrente y metastásica, aunque no se ha evidenciado un claro beneficio en la supervivencia.…”
Section: Pág 11343unclassified
“…Penelitian tersebut memiliki rentang sampel penelitian dari usia 20-71 tahun dengan jumlah kasus terbanyak ada pada kelompok usia 40-49 tahun, yaitu sebanyak 28 pasien. 11 Studi histopatologi yang dilakukan di B.P Koirala Memorial Cancer Hospital menemukan hasil yang serupa pada klasifikasi kelompok usia sesuai dekade. Studi tersebut melaporkan bahwa jumlah kasus tumor payudara terbanyak ditemukan pada kelompok usia 40-49 tahun, yaitu sebanyak 31,2% dari total sampel.…”
Section: Pembahasanunclassified